Development of Contextual Teaching and Learning (CTL) Oriented Student Worksheets (LKPD) on Digestive System Material for Class XI High School - Rahmadani Rahmadani; L Lufri; Muhyiatul Fadilah; Rahmadhani Fitri (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2021)
Implementation of learning is one of the main tasks of teachers to teach students. The intended learning is the creation of conditions that allow it to occur in students. Learning will improve cognitive, affective, and psychomotor abilities, these abilities are accompanied by experience gained during the learning process that applies anywhere and anytime and can be applied in everyday life. One of the materials for class XI that is difficult for students to understand is the material on the digestive system. One way that can be done is to make it easier for students to understand the material on the digestive system by developing Contextual Teaching and Learning (CTL) oriented student worksheets teaching materials, with this worksheet students can relate learning materials to everyday life. Student worksheet (LKPD) development is carried out using 3 stages of 4-D model development. The stages are defined, design, and develop. The data collection instruments used were validity and response questionnaires. The student worksheets were validated by 3 validators and a response test was conducted on 25 students of class XI and one Biology teacher at SMA Negeri 2 Lembang Jaya. This research produces student worksheets with Contextual Teaching and Learning (CTL) orientation on the digestive system material for class XI. The results of the validity of the student worksheets obtained 91.78% with very valid criteria both in terms of the feasibility of content, language, presentation, and graphics. The results of the teacher's assessment of the practicality of the student worksheets obtained an average of 93.28% with practical criteria and an average student assessment of 86.65% with very practical criteria in terms of ease of use, efficient learning time, and benefits. It can be concluded that the student worksheets (LKPD) oriented to Contextual Teaching and Learning (CTL) with a valid category and the responses of teachers and students about its practicality are included in the very practical category.